METHOD OF ESTABLISHING THE CRITERIA OF KAFAAH AS THE FOUNDATION OF A HARMONIOUS FAMILY FROM THE PERSPECTIVE OF FIKIH MUNAKAHAT - Gulo, Azhar Nur Mawaddah; Adly, Muhammad Amar (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2026)
This study examines the method of determining the criteria for kafaah from the perspective of munakahat fiqh as the main foundation for realizing a sakinah family. Kafaah is defined as equality, harmony, or balance between couples who are about to marry to maintain harmony and protect women's rights from the risk of household failure. Legally, Article 61 of the Compilation of Islamic Law emphasizes that religious differences cannot be a barrier to marriage. Scholars from four schools of thought differ on what is considered the elements of kafaah, including freedom, property, profession, and lineage. However, they all agree that the quality of religiosity and morals are the most important requirements. Religion is seen as a pillar of stability because it can guide the soul in facing household problems and prevent the emergence of caste or social stratification that contradicts the principle of piety, as mentioned in QS. Al-Hujurat verse 13. To evaluate the tension between classical texts and contemporary sociological realities, this study uses a qualitative descriptive-analytical and juridical-normative approach. Research shows that kafaah is a customary requirement for marriage, not a legal requirement. This allows women and their guardians to choose an equal partner to achieve a harmonious, stable, and lasting marriage.Keywords: kafaah criteria, sakinah family, munakahat fiqh perspective.